Financial Performance Policies During Recovery Period: A Case Study of Bank BJB, a Public Regional Development Bank in Indonesia Company - Phelia Irma Indriani Badrudin; Syifa Rachmania Komara (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyse Bank BJB's financial performance using operating cash flow ratios: OCF/CL, OCF/TD, and OCF/NP. Methodology: A descriptive quantitative approach was applied using secondary data from Bank BJB's audited annual reports for 2019-2023, covering the pre-pandemic, pandemic, and recovery phases. The data were analysed using operating cash flow ratio analysis, with a benchmark value of 1, to assess liquidity pressure, debt dependency, and earnings quality. Results: The results show unstable cash-based financial resilience, with average OCF/CL, OCF/TD, and OCF/NP ratios of -0.011, -0.009, and -0.513, respectively. These findings indicate that operating cash flow was insufficient to support current liabilities, total liabilities, and net profit. Although 2021 recorded the strongest performance, the sharp decline in 2022 confirms that profitability was not always aligned with actual cash generation. Findings: The findings highlight the importance of cash-flow-based control and the need to align credit expansion with operating cash flow capacity. Novelty & Originality: This study offers novelty by analysing operating cash flow ratios across pre-pandemic, pandemic, and recovery phases for Bank BJB, a context rarely explored in prior research on Indonesian regional banks. Conclusions: Bank BJB needs to strengthen cash-flow-based control by aligning credit expansion with operating cash flow capacity, maintaining third-party fund stability, and ensuring that digital transformation improves cost efficiency and sustainable cash generation. Type of Paper: This paper is an empirical research paper.